Why are some nations more entrepreneurial than others? Investigating the link between cultural tightness–looseness and rates of new firm formation - Assenova, Valentina A.; Amit, Raphael (Strategic Entrepreneurship Journal, 2025)
Abstract Research Summary We evaluate the role of cultural tightness–looseness as an explanation for cross‐cultural variation in new firm formation rates. Modeling cultural tightness–looseness as an antecedent for individual entrepreneurial dispositions and informal institutions, we examine its impact on the number of new limited‐liability companies registered per 1000 people and the rate of new entrepreneurs in the working‐age population. Our findings show that cultural tightness–looseness explains 56% of the variation in new firm formation rates in a sample of 156 nations, and 71% of the variation in the rate of new entrepreneurs in the 50 US states, with greater cultural looseness corresponding to higher rates of entrepreneurship, on average. This effect is robust to various model specifications, measures, and controls for other cultural dimensions. Managerial Summary Our study examines how cultural tightness–looseness impacts new firm formation rates across nations and US states. We find that cultural looseness, characterized by flexible social norms, significantly influences entrepreneurial activity. Specifically, it explains 56% of the variation in new firm formation rates across 156 nations and 71% of the variation in new entrepreneur rates in the 50 US states. Nations and states with looser cultures tend to have higher rates of entrepreneurship. These findings are robust across different model specifications, measures, and control variables. Managers and policymakers should consider the strength and enforcement of social norms as factors in fostering new firm formation.